Changes in plasma volume following intense intermittent exercise in neutral and hot environmental conditions - Rotstein, A; Falk, B; Einbinder, M; Zigel, L (Journal of sports medicine and physical fitness, 1998)
The purpose of the present investigation was to examine the effect of supramaximal short duration intermittent exercise in neutral and hot environmental conditions on changes in plasma volume. The return of plasma volume (PV) to pre-exercise values following different recovery conditions was also examined. Experimental design. Within subject design in which one way analysis of variance was conducted. Research, sports science academic institute. Ten trained men, 25.5 +/- 3/1 (yrs), volunteers. Subjects performed six 1-min bouts of exercise at 100% VO2peak on a cycle ergometer, with 4-min rest intervals between the bouts. Each subject exercised twice in thermoneutral (22 degrees C, 40% RH) and twice in hot (35 degrees C, 30% RH) conditions. Exercise was followed by either 40 min of passive recovery (sitting) or by 20 min active recovery (cycling at 35% VO2peak) and 20 min passive recovery, named thereafter "active recovery". Hematocrit (Hct) and hemoglobin (Hb) were determined upon entry into the climatic chamber following 20 min rest in the chamber (pre-exercise), immediately postexercise, and 40 min postexercise. From the changes in Hct and Hb, PV changes were calculated. There was a significant decrease in PV immediately postexercise. However, there was no significant difference between the two types of environmental conditions and no difference between the two types of recovery. PV increased significantly following recovery and returned to pre-exercise values following 40 min of recovery. Changes in PV caused by maximal short duration cycling bouts is not affected by environmental conditions, PV returns to its pre-exercise values within 40 min of recovery regardless of the recovery mode.